2017
DOI: 10.1111/grs.12173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling corn stover with legume herbages in different proportions on fermentation characteristics, nutritive quality and in vitro digestibility on the Tibetan Plateau

Abstract: In order to evaluate the nutritional value and digestibility of corn (Zea mays L.) stover silage mixed with legume herbages in Tibet, corn stover was ensiled with four levels (0, 10, 20 and 30% of fresh weight) of common vetch (Vicia sativa L.) and alfalfa (Medicago sativa L.), respectively. The silos were opened after 45 days of ensiling, and the fermentation characteristics, nutritive quality and in vitro digestibility of the mixed silages were analyzed. The results showed that the inclusion of legumes could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 29 publications
4
50
2
Order By: Relevance
“…These results were in accordance with Filya et al [23], who found WSC remaining in alfalfa silage were significantly higher in non-inoculated control than those in the LAB-inoculated counterpart after ensiling. During ensiling M silage showed highest WSC concentration, which might be attributed to the weak conversion efficiency of WSC by epiphytic LAB resulting in more WSC being retained in the silage [24].…”
Section: Controlmentioning
confidence: 99%
“…These results were in accordance with Filya et al [23], who found WSC remaining in alfalfa silage were significantly higher in non-inoculated control than those in the LAB-inoculated counterpart after ensiling. During ensiling M silage showed highest WSC concentration, which might be attributed to the weak conversion efficiency of WSC by epiphytic LAB resulting in more WSC being retained in the silage [24].…”
Section: Controlmentioning
confidence: 99%
“…Buffering capacity and ammonia nitrogen (NH 3 -N) were determined according to Chen et al (2014). Organic acid contents were analyzed according to Wang et al (2017).…”
Section: Chemical and Microbial Analysesmentioning
confidence: 99%
“…It is thus significant to explore the micro‐organism resource on the Tibetan Plateau. However, the cold and arid continental climates, poor soil and short growing seasons limit the forage yield in most areas of Tibet, resulting in malnutrition and poor production performance of livestock (Wang, Yuan, Dong, Li, & Shao, ). Therefore, forage preservation is a desirable strategy for sustainable development of livestock production in Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…Buffering capacity and ammonia nitrogen (NH 3 -N) were determined according to Chen et al (2014). Organic acid contents were analysed according to Wang et al (2017).…”
Section: Chemical and Microbial Analysesmentioning
confidence: 99%